Redemption, Kansas [large type] - Reasoner, James (Wheeler Publishing large print western, 2011)
The town of Redemption surely does need some-- especially with a crooked marshal in charge. Texas cowhand Bill Harvey is laid up in Kansas, waiting to heal. But the longer he stays in Redemption, the more he gets the feeling that there's something wrong. A series of unexplained killings has local shopkeepers fearing for their lives-- and it's up to Bill to figure out what's wrong.